2002
DOI: 10.1159/000059430
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptor Subtypes 2 and 5 Inhibit Corticotropin-Releasing Hormone-Stimulated Adrenocorticotropin Secretion from AtT-20 Cells

Abstract: Somatostatin (SRIH) regulates pituitary adrenocorticotropin (ACTH) secretion by interacting with a family of homologous G protein-coupled membrane receptors. The SRIH receptor subtypes (sst1–sst5) that control ACTH release remain unknown. Using novel, subtype-selective SRIH analogs, we have identified the SRIH receptor subtypes involved in regulating ACTH release from AtT-20 cells, a model for cell line pituitary corticotropes. Radioligand-binding studies with 125I-SRIH-14 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 31 publications
(53 reference statements)
5
38
0
Order By: Relevance
“…To evaluate ACTH secretory response to CRH in vitro, AtT20/D16v-F2 cells were incubated for 0, 2, 5, 10, 15, and 30 min with CRH at 100 nM, a concentration at which CRH is known to induce ACTH secretion in these cells (Strowski et al 2002). ACTH was then assayed in the condition medium.…”
Section: Effects Of Mitotane On Crh-stimulated Acth Secretionmentioning
confidence: 99%
“…To evaluate ACTH secretory response to CRH in vitro, AtT20/D16v-F2 cells were incubated for 0, 2, 5, 10, 15, and 30 min with CRH at 100 nM, a concentration at which CRH is known to induce ACTH secretion in these cells (Strowski et al 2002). ACTH was then assayed in the condition medium.…”
Section: Effects Of Mitotane On Crh-stimulated Acth Secretionmentioning
confidence: 99%
“…Among them are the sst2-prefering agonist octreotide, and the multireceptor ligand SOM230 which binds to sst1, sst2, sst3 and sst5 with high affinity, having a 30, 5 and 40 fold higher affinity to sst1, sst3 and sst5 receptors, respectively, compared with octreotide (4). It has been reported that sst2-and sst5-specific agonists inhibit CRH-induced ACTH release from AtT-20 cells (5). Although individual clinical case reports indicate that octreotide was able to restore eucortisolemia in patients presenting with an ACTH-dependent Cushing's syndrome (6), the efficacy of the sst2-prefering agonist, octreotide, could not be established in clinical trials (7).…”
Section: Introductionmentioning
confidence: 99%
“…IC 50 values of inhibition suggested a sst 5 -like response of ACTHinhibition. Both sst 2 and sst 5 are involved in the inhibition of ACTH release and cAMP production in AtT20 cells [56] and a functional superiority of sst 5 over sst 2 has been suggested by others as well [57,58]. On the other hand, sst 2 receptors, albeit at low level, are co-expressed with sst 5 receptors in corticotroph adenomas as well.…”
Section: Role Of Somatostatin and Its Analogs On Acth Secretion By Comentioning
confidence: 76%